(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Oral anticoagulation with warfarin is challenging owing to the drug’s narrow therapeutic index. Achievement of therapeutic range ensures safety and efficacy of warfarin therapy. A retrospective study of four hundred and six patients on warfarin anticoagulation was conducted at Kenyatta National Hospital, Kenya for the period between January 2014 and June 2016. The percentage of follow-up time spent in therapeutic international normalized ratio range was computed by Rosendaal linear interpolation method. Factors associated with this time were also explored. The mean age of the participants was 42.7±16.9 years and the ratio of females to males was 3:1. The mean percentage of time spent in therapeutic international normalized ratio range was 31.1%. Poor anticoagulation control was associated with congestive heart failure (p=0.047) and the independent predictor of time in therapeutic range was renal dysfunction (β= -13.3, 95% CI: -25.9, -0.8, p=0.038) suggesting that management of these patients needs to be intensified.